Estrategias didácticas para fortalecer el Desarrollo Emocional en niños y niñas de Educación Inicial - Carpio Benítez, Keyna Coraima (2022)
This current focused on solving the following problem: How to strengthen the emotional intelligence development intro children from Initial Education? And it is projected as a general aim: to elaborate a methodological strategies didactic guide to strengthen the emotional intelligence development intro Initial Education children from Salcedo Educational Unit", by starting from a previous made diagnosis by Taguada and Sagñay in the 2022 year with the topic: "Emotional Intelligence Development in the children Teaching-Learning Process intro of Initial Education", what they tag, which emotions intervene into relationship with others and that they must occupy a space within learning. Since the methodological is assumed a qualitative approach and the inductive method to draw the conclusions, documentary analysis to work on the background, modeling to elaborate the proposal and expert criteria for validation. Working on the Emotional Intelligence development is essential due to because it has many benefits into educational settings, favoring in children the recognition, understanding and emotions expression into a correct way, in order for facilitating relationships with others and improves the Initial education teaching-learning processes. The proposal is presented, through a methodological guide as a tool for teachers with strategies, activities and resources for initial education children for strengthening educational quality around the Emotional Intelligence development in the classroom, in this sense, recreation and playful are essential to create scenarios focused about emotional education and after submitting the guide to a validation process, it is denoted the activities relevance into emotional development and a correct application beneficiary or all educational community members and specifically children.